R1234yf vs R134a in automotive air conditioning system: A comparison of the performance - Sharif, M. Z.; Azmi, W. H.; Zawawi, N. M. M.; R., Mamat; Hamisa, A. H. (IOP Publishing, 2020)
The main objective of this study is to evaluate the performance of a compact automotive air conditioning (AAC) system operating with R1234yf and R134a refrigerant. The different ranges of initial refrigerant charge and compressor speed have been tested on the AAC to evaluate the effect of different refrigerant on the thermodynamic performance. The results of this study have shown that the cooling capacity of R1234yf AAC system is significantly lower (between 5 to 25 %) than R134a system. In the experiment, the power of the compressor is slightly lower (up to 11 %) for refrigerant R1234yf compared to R134a inside the AAC system. Finally, the experimental results reveal that, under the same operating conditions, the COP of R1234yf AAC system is always lower than with R134a (14.5 % on average). In order to maximize the efficiency and performance of AAC system, further optimization needs to be done in order to reduce the gap in term of performance of the AAC system operating with R1234yf refrigerant.